Exploring the Relationship between Prophetic Leadership and Job Satisfaction of Madrasah Ibtidaiyah Teachers in Indonesia - Juhji, Juhji; Rahmatullah, Mamat; Noor, Wahyudin; Zuhri, Saefudin; Mansur, Mansur; Nuangchalerm, Prasart (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study examined the relationship between prophetic leadership and job satisfaction among Madrasah Ibtidaiyah teachers in Indonesia. The research method used a quantitative research design with survey techniques. Data were collected from 179 facilitator teachers in 27 provinces using a validated Likert scale questionnaire. Data analysis used regression tests to assess the effect of prophetic leadership on job satisfaction. Findings showed a significant positive correlation, indicating that a 1% increase in prophetic leadership was associated with a 0.514 increase in job satisfaction. It suggests that enhancing the principles of prophetic leadership within an education management framework can significantly improve teachers' well-being and the overall quality of education in Madrasah Ibtidaiyah. This study underscores the importance of integrating moral and spiritual dimensions into Islamic education, encouraging a more inclusive and dignified work environment for educators. The implications of the findings advocate a shift towards a leadership model that prioritizes ethical considerations, potentially leading to sustainable improvements in educational practices and outcomes.